DECISION MAKING SYSTEM USING THE TOPSIS METHOD IN DETERMINING THE POSITION OF ASN EMPLOYEES - Marjones H. H Sihombing; Ika Yusnita Sari; Elvika Rahmi; Khairunnisa (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2023)
The implementation of decision support systems in Indonesia, especially in the Management of State Civil Apparatus (ASN), has been mandated. The regulations contain criteria and procedures for assessing the extent to which government agencies have implemented decision support systems in ASN Management. The application of the SPK itself is to ensure that positions in the government bureaucracy are occupied by employees who meet the qualification and competency requirements. So that the goal of development, especially in the field of human resource personnel, is to create ASN that is professional, has high performance, has integrity and upholds neutrality, can be realized. From previous observations, a decision support system was created in determining ASN positions. The method used is Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) which can help provide recommendations for ASN positions. It is hoped that the use of the Decision Support System (DSS) can help decisions taken in selecting and determining who is the best employee to obtain an ASN employee position, considering that so far they have not used a particular method in selecting ASN employee positions so that sometimes decisions are considered less objective and inappropriate. target. This method can be used to determine the position of ASN employees in this assessment. This can facilitate decisions proportionally based on the results of employee data processing including experience, education, length of service, age, relevance of position precisely and accurately because the system can minimize errors in the data normalization calculation process.